Spatial Modelling of Indoor Air Pollution Distribution at Home. Issue 1 (1st June 2022) - Putri, A N A R; Salam, R A; Rachmawati, L M; Ramadhan, A; Adiwidya, A S; Jalasena, A; Chandra, I
Abstract: In ancient times, humans were very accustomed to depending on nature, so that in the past humans held the title as an outdoor species. Over time with many technological advances, the pattern of human life has shifted to being an indoor species. Currently, almost 55% of the world's population lives in urban areas and is projected to increase to 68% by 2050. Based on the National Human Activity Pattern Survey (NHAPS), the total time humans spend indoors is 86.9%. Research shows that air pollutants contained in indoor air are 2 to 5 times more than outdoor air. The neglect of the air conditioning system also worsens indoor air quality. It is often found that the supply of fresh air and the concentration of pollutants in the work or activity zone is unknown, even though this is a crucial matter. With the amount of time spent indoors, air quality and the distribution of pollutants in indoor air becomes very important. This research was conducted spatial modelling of air pollutant distribution using the kriging interpolation technique. The results of spatial modelling with this method produce an average of R-squared=70, 98% dan RMSE = 0.03. Several factors influence the increase in pollutant concentrations that are the activity of the occupants, the number of occupants, and environmental conditions outside.